(untitled) (African Journal of Biomedical Research, 2020)
This study set out to identify the unhealthy lifestyle habits adopted by nurses at the University College Hospital (UCH), Ibadan which could predispose to Cardiovascular diseases (CVDs) and assess the cardiovascular risk factors among them. A cross sectional study design was utilized. The study population consisted of nurses working on the wards at the UCH, Ibadan who were between the ages of 30-60 years. Systematic random sampling was adopted in selecting 196 nurses for this study. A structured questionnaire was administered to consenting nurses. Focus group discussions were conducted to further probe into the details of the questionnaire. 94.9% of respondents were female and the mean age of respondents was 39.3±7.4 years. About 32% of the respondents engaged in moderate exercise less than once a week, 59% of the respondents slept between 5-6 hours at night, 44.9% ate fried food 1-2 times weekly, 42.9% consumed one or more litres of soda drink per week. Majority demonstrated high level of awareness about cardiovascular risk factors such as cigarette smoking (78.1%), alcohol use (76.5%), overweight/obese (75.5%), high blood cholesterol (73.5%), physical inactivity (71.9%) and diabetes mellitus (70.9%). However, there was a low level of awareness about cardiovascular risk factors such as race (41.3%) and gender (34.2%). A significantly higher proportion (70%) of respondents who ate fried foods on an average of 3-6 times per week were overweight/obese (p=0.016). Obesity was also associated with family history of cardiovascular diseases (p=0.04). The focus group discussions highlighted nurses’ views about difficulties in practicing known healthy lifestyle habits. The study highlighted a moderate prevalence of cardiovascular risk factors such as obesity, consumption of fried foods and physical inactivity among nurses. Efforts should be directed towards the promotion of healthy lifestyles among nurses.